Construction and evaluation of Bordetella pertussis live attenuated vaccine strain BPZE1 producing Fim3. Issue 11 (7th March 2018) - Debrie, Anne-Sophie; Coutte, Loïc; Raze, Dominique; Mooi, Frits; Alexander, Frances; Gorringe, Andrew; Mielcarek, Nathalie; Locht, Camille
Abstract: Pertussis or whooping cough is currently the most prevalent vaccine-preventable childhood disease despite >85% global vaccination coverage. In recent years incidence has greatly increased in several high-income countries that have switched from the first-generation, whole-cell vaccine to the newer acellular vaccines, calling for improved vaccination strategies with better vaccines. We have developed a live attenuated pertussis vaccine candidate, called BPZE1, which is currently in clinical development. Unlike other pertussis vaccines, BPZE1 has been shown to provide strong protection against infection by the causative agent of pertussis, Bordetella pertussis, in non-human primates. BPZE1 is a derivative of the B. pertussis strain Tohama I, which produces serotype 2 (Fim2) but not serotype 3 fimbriae (Fim3). As immune responses to fimbriae are likely to contribute to protection, we constructed a BPZE1 derivative, called BPZE1f3, that produces both serotypes of fimbriae. Whereas nasal vaccination of mice with BPZE1 induced antibodies to Fim2 but not to Fim3, vaccination with BPZE1f3 elicited antibodies to both Fim2 and Fim3 at approximately the same level. In mice, both BPZE1 and BPZE1f3 provided equal levels of protection against clinical isolates that either produce Fim2 alone, both Fim2 and Fim3, or no fimbriae. However, vaccination with BPZE1f3 provided significantly stronger protection against Fim3-only producing B. pertussis than vaccination with BPZE1, indicating that immune responses to fimbriae contribute to serotype-specific protection against B. pertussis infection.